New campus-Save Mart Center-0036 (2000)
First $3 million donation by Pepsi and Save Mart Center (L-R) Arakel Arisian assoc. students pres. Brian Spearman VP retail sales-Pepsi, Al Bahl-Ath Dir. Bob Piccinini chair and Pres Save Mart and Pres. John Welty Photo by Eusevio Arias